THE STUDENTS COGNITIVE DISCREPANCIES IN ARTIFICIAL INTELLIGENCES UTILIZATION: A CASE OF HIGHER LEARNING INSTITUTIONS - Shima Dawson Banele (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2023)
The humanistic intellectual algorithmic nodes deployment on Artificial Intelligences (AIs) brought significances in undertaking socio-economics activities. Students in higher learning institutions utilized the AIs for education purposes leading to damages in the cognitive process. The phenomenography action research was purposively conducted to assess 113 higher learning institution students’ cognitive discrepancies due to AI utilization. The objectives undertaken were to: assess the attributes leading students’ differences in AI utilization and determine the students cognitive discrepancies in performance resulted by utilization of AI in the learning process. Data were collected through students’ test-re-tested class activity worksheets observations and semi-structured interview. The major findings showed that students were highly rated in utilization of AI to save time, had cognitively worries and less authentic assurance. Also, the findings on students cognitive discrepancies utilization was proved to be ascertained on indicators for cognitive processes, individual differences, feedback and interaction, motivation and engagement, creativity and imagination. The recommendation were made to students and instructors to appropriate utilize and blend AI utilization in teaching and learning process for cognitive wealth so as to overwhelm shortfalls resulted by over utilization of AIs.